Cognitive Function in Pediatric Hypoplastic Left Heart Syndrome: Systematic Review and Meta-Analysis. (9th May 2019) - Siciliano, Rachel E; Prussien, Kemar V; Lee, Chelsea A; Patel, Niral J; Murphy, Lexa K; Compas, Bruce E; Jordan, Lori C
Abstract: Objective: Despite surgical palliation, children with hypoplastic left heart syndrome (HLHS) have compromised cardiac functioning and increased risk for cognitive deficits. We quantitatively reviewed the empirical data from this literature. Methods: The present meta-analysis included 13 studies reporting cognitive function for children with HLHS between the ages of 2 years and 6 months and 17 years that used standardized assessments of Full Scale IQ (FSIQ), Verbal IQ (VIQ), and Performance IQ (PIQ). Differences in cognitive function were assessed relative to normative data, and we examined sample mean age and publication year as moderators. Results: Large effects were found for FSIQ ( g = −.87, 95% CI [−1.10, −.65], M = 86.88) and PIQ ( g = −.89, 95% CI [−1.11, −.68], M = 86.56), and a medium effect was found for VIQ ( g = −.61, 95% CI [−.84, −.38], M = 90.82). All models demonstrated significant heterogeneity. Meta-regression analyses of effect size via Hedges' g on child age revealed a significant effect on FSIQ (coefficient = −.07, 95% CI [−.12, −.01], p < .01, R 2 = .40) indicating a loss of 1.1 FSIQ points across studies with each increased year of mean sample age. Conclusions: Deficits in FSIQ may reflect chronic brain injury or failure to make expected gains as children age. This review highlights the importance of early intervention in this population, and the need for longitudinal studies analyzing more specific domains of cognitive function and potential moderators.